Perbandingan Hukum Pidana Perzinaan di Malaysia dan Brunei Darussalam - Sudarti Sudarti (El-Mashlahah, 2021)
Malaysia and Brunei Darussalam are country which is being in  Southeast Asia Area, the majority is population of religion islam. Both of them have equality and difference in applying islamic law about criminal sanction in adultery such as contained in Enakmen Jenayah Syariáh Selangor Number 9 in 1995 and Kanun Jenayah Syariáh Brunei Darussalam.  The research is aim to analysis the problem of criminal sanction in adultery Enakmen Syariáh Selangor Number 9 in 1995 and Kanun Jenayah Syariah Brunei Darussalam that used maqasid syariah such as methodology. Type of research will  be used library research by  analytical descriptive method. The results show the aspect of daruriyyah, who applied by punishment for the adultere are the aspect of keeping offspring  (hifdz al-asl). The aspect is related to children’s rights and  the civil relationship between a child with their biological parents.Keywords: the crime of adultery, Enakmen Jenayah Syari'ah Selangor Number 9 of 1995, Kanun Jenayah Syari'ah Brunei Darussalam, maqasid ash-sharia.Malaysia dan Brunei Darussalam merupakan negara yang berada di kawasan Asia Tenggara yang memiliki penduduk yang mayoritasnya beragama Islam. Kedua wilayah ini memiliki persamaan maupun perbedaan dalam pemberlakuan syariat Islam tentang penerapan sanksi tindak pidana perzinaan di wilayahnya sebagaimana yang terdapat dalam Enakmen Jenayah Syari’ah Selangor Nomor 9 Tahun 1995 dan Kanun Jenayah Syari’ah Brunei Darussalam. Penelitian ini bertujuan untuk menganalisis persoalan tindak pidana perzinaan dalam Enakmen Jenayah Syari’ah Selangor Nomor 9 Tahun 1995 dan Kanun Jenayah Syari’ah Brunei Darussalam dengan menggunakan maqa>s{id asy-syari>’ah. Jenis penelitian yang digunakan adalah penelitian pustaka dengan metode deskriptif analitis. Hasil penelitian menunjukkan bahwa aspek d{aru>ri>yyat yang berkenaan dengan hukuman bagi pelaku zina adalah aspek pemeliharaan keturunan (h{ifż al-nasl). Aspek ini merupakan aspek yang berkaitan dengan hak-hak anak dan hubungan keperdataan seorang anak dengan orangtua kandungnya, dalam hal ini adalah ayah biologisnya.Kata Kunci: tindak pidana perzinaan, Enakmen Jenayah Syari’ah Selangor Nomor 9 Tahun 1995, Kanun Jenayah Syari’ah Brunei Darussalam, maqa>s{id asy-syari>’ah.